Nickel allergy in lipid transfer protein sensitized patients: Prevalence and clinical features - Rizzi, Angela; Chini, Raffaella; Inchingolo, Riccardo; Carusi, Valentina; Pandolfi, Franco; Gasbarrini, Antonio; Nucera, Eleonora (International journal of immunopathology and pharmacology, 2020)
Nickel (Ni), the main responsible for allergic contact dermatitis worldwide, is also involved in systemic condition called “Systemic Nickel Sulfate Allergy Syndrome (SNAS).” Likewise, IgE-mediated reactivity to Lipid Transfer Protein (LTP) represents the main cause of primary food allergy in adults of Mediterranean countries. We evaluated the prevalence of SNAS in LTP allergic patients and investigated patients’ clinical features with double sensitization (LTP and Ni). A retrospective, single-center, observational study was conducted performing a complete allergological work-up including: (1) skin prick tests; (2) serum specific IgE for plant food allergens and rPru p3 (LTP); (3) patch test with 5% Ni sulfate in petrolatum. We enrolled 140 LTP allergic patients of which 36 patients (25.7% of sample) showed additional positivity to Ni patch test. Patients with double sensitization were more frequently females and reported fewer cutaneous symptoms. Higher values of sIgE for peach, apple, peanut, walnut, grain, corn, and garlic were found in LTP allergic patients, while higher values for hazelnut in the other subgroup. The prevalence of SNAS in the LTP allergic population is clinically relevant. Moreover, the clinical and immunological profiles of patients with double sensitization were different from patients monosensitized to LTP.